Functional fillers and nanoscale minerals : new markets/new horizons - Kellar, Jon J. (Society for Mining, Metallurgy, and Exploration, Inc. (SME), 2006)
The emergence of nanoscale minerals parallels the global pursuit of nanotechnology. The use of these minerals plays an important role in low-cost, high-performance application of nanotechnology. This 21-chapter compilation is for mineral suppliers, industrial users of mineral fillers, and those concerned with new trends in mineral processing and nanotechnology.